The Value of CTA Based on Gold Nanorod Contrast Agent in Coronary Artery Diagnosis and Plaque Property Analysis - Heyu Bi (Hindawi Limited, 2021)
Coronary CT angiography (CTA) with the characteristics of noninvasive and simple operation is widely used in the diagnosis of coronary artery stenosis. The choice of contrast agent exerts an important impact on the imaging quality of CTA. Conventional iodine contrast agents are easily excreted by the kidneys, from which the imaging window is short, and the imaging quality is poor. Metal nanomaterials have unique optical properties and have broad application prospects in imaging. Our aim is to explore the value of gold nanorod contrast agent in the diagnosis of coronary heart disease. A gold nanorod suspension was first prepared, and the prepared gold nanorod was uniform and had good dispersibility. It can be seen from the light absorption curve that there are two obvious peaks on the UV absorption peak of the gold nanorods. The gold nanorods were cultured in different solutions, and it was found that the particle size of the gold nanorods did not change significantly within 72 hours, indicating that the prepared gold nanorods had good stability. When observing the damage degree of mouse kidney tissue, it was shown that the damage degree of gold nanorod contrast agent to mouse kidney tissue was less than that of iodine contrast agent. The above results indicate that the gold nanorod contrast agent has good stability and safety. Therefore, our study demonstrated that the gold nanorod contrast agent has high value in the diagnosis of coronary arteries and the analysis of plaque properties.